An estimated DSGE model for Denmark with housing, banking, and financial frictions - Jesper Pedersen (Danmarks Nationalbank, 2016)
An Estimated DSGE model for Denmark with Housing, Banking, and Financial Friktions The financial crisis has moved attention to the modeling of financial frictions and banks in DSGE models. The preceding housing boom put focus on the need to incorporate developments in the residential sector, including house prices. This paper documents an estimated DSGE model of the Danish economy with financial frictions, banking and a construction sector. – – En Estimeret DSGE model for Danmark med boliger, finansiel sector og finansielle friktioner Den finansielle krise satte fokus på nødvendigheden af at modellere finansielle friktioner og en finansiel sektor i DSGE modeller. De forudgående stigninger i boligpriserne satte fokus på nødvendigheden af at kunne analysere boligmarkedet og mulige samspil mellem denne og den øvrige realøkonomi. Dette arbejdspapir dokumenterer en estimeret DSGE model for dansk økonomi med finansielle friktioner, finansiel sektor og byggesektor.
Keywords: E17; E32; E62; E65; F41; 330; DSGE Models; Estimation; Financial frictions; Banking